2017
DOI: 10.1021/jacs.7b07788
|View full text |Cite
|
Sign up to set email alerts
|

Switching between Plasmonic and Fluorescent Copper Sulfide Nanocrystals

Abstract: Control over the doping density in copper sulfide nanocrystals is of great importance and determines its use in optoelectronic applications such as NIR optical switches and photovoltaic devices. Here, we demonstrate that we can reversibly control the hole carrier density (varying from >1022 cm–3 to intrinsic) in copper sulfide nanocrystals by electrochemical methods. We can control the type of charge injection, i.e., capacitive charging or ion intercalation, via the choice of the charge compensating cation (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 53 publications
3
93
0
Order By: Relevance
“…In the big family of Cu chalcogenide compounds, Cu vacancies commonly exist by ambient exposure, [34] which probably stems from its superionic nature [35] and thus weak Cu-S bonding. The deficiency of Cu ions, which serve as electron donor in semiconductor, leads to the self-doping of high density (up to 10 21 cm −3 ) holes in Cu 2−x S. [36] Consequently, in theory the conductivity of Cu 9 S 5 is high. The electrical transport property of the Cu 9 S 5 nanoflakes was measured using a back-gated FET configuration on a p-type silicon substrate that was covered by 300 nm thick SiO 2 as dielectric layer.…”
Section: Synthesis and Characteristics Of The Cu 9 S 5 Nanoflakesmentioning
confidence: 99%
“…In the big family of Cu chalcogenide compounds, Cu vacancies commonly exist by ambient exposure, [34] which probably stems from its superionic nature [35] and thus weak Cu-S bonding. The deficiency of Cu ions, which serve as electron donor in semiconductor, leads to the self-doping of high density (up to 10 21 cm −3 ) holes in Cu 2−x S. [36] Consequently, in theory the conductivity of Cu 9 S 5 is high. The electrical transport property of the Cu 9 S 5 nanoflakes was measured using a back-gated FET configuration on a p-type silicon substrate that was covered by 300 nm thick SiO 2 as dielectric layer.…”
Section: Synthesis and Characteristics Of The Cu 9 S 5 Nanoflakesmentioning
confidence: 99%
“…9 Stam et al reported that Cu + ions intercalation leads to permanent phase transition from CuS to Cu 2 S NCs, whereas Li + ions interaction leads to reversible transition between CuS and CuLiS structures. 18 Recently, Liu et al reported the reversible nanoscale interconversion from CuS to Cu 2 S nanocrystals (NCs) and vice versa. 14 It is well known that Hg 2+ ions have strong affinity towards sulfur ligands and sulfur anions (S 2À ) due to so-so interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Copper monosulfide (CuS) has distinguished itself among metal sulfides owing to its different band gap and various morphologies. This makes CuS a hot-spot semiconductor material with great potential in the field of photocatalytic and photovoltaic applications [18][19][20][21][22][23][24][25][26]. Hexagonal covellite-CuS with a bandgap of ∼2 eV and a p-type-enhances absorber abilities to cover the entire solar spectrum [18,19].…”
Section: Introductionmentioning
confidence: 99%